Dynamic analysis of a stiffened composite plate under blast load: A new model and experimental validation - Balkan, Demet; Demir, Ozgur; Arikoglu, Aytac (PERGAMON-ELSEVIER SCIENCE LTD, 2020)
In this paper, the nonlinear dynamic behavior of a laminated composite plate with sandwich stiffener subjected to the non-uniform blast load is investigated. The main plate examined has four layers carbon/epoxy and the stiffeners composed of carbon/epoxy face sheets and polypropylene honeycomb core. The experimental and theoretical studies are carried out in order to investigate the effect of sandwich stiffeners on the dynamic response of laminated composite plates under the blast load. In the theoretical study, the equations of motion of the stiffened laminated composite plate are derived by the use of virtual work principle. Geometric nonlinearities are modelled by taking von Karman Large Deformation Theory into account for the sandwich plate. The clamped boundary conditions are considered for all edges of the plate. The equations of motion are discretized into the time domain by using Galerkin's method. The nonlinear coupled equations system is solved by NDSOLVE function of Mathematica Software and the displacements, strains and stresses are calculated in order to investigate the stiffened laminated composite plate's response to the blast load. The experimental, theoretical and numerical analysis results are compared.
Keywords: Non-uniform blast load; Stiffened composite Plate; Galerkin's method; SANDWICH PANELS; RECTANGULAR-PLATES; PERFORMANCE; VIBRATIONS; DEFORMATION; BEHAVIOR; IMPACT; AIR; Engineering; Mechanics